Optimization of Polyetherimide Based CMS Membranes Preparation Conditions for CO2/CH4 Selectivit - Ahmad, M. A.; Rashid, N. K. A.; Hameed, B. H. (Journal of Applied Membrane Science & Technology, 2017)
Response surface methodology (RSM) was used to determine the optimum preparation conditions of polyetherimide based carbon molecular sieve (CMS) membranes. Two quadratic models were developed to correlate the pyrolysis temperature, pyrolysis time and polymer concentration to the responses; CO2 permeance and CO2/CH4permselectivity. According to the optimization analysis, the optimum preparation conditions were obtained by using pyrolysis temperature of 725°C, pyrolysis time of 3.0 h and polymer concentration of 8.52%, which resulted in CO2 permeance and CO2/CH4 permselectivity of 3.61×10–10 mol/m2.s.Pa and 4.35, respectively.